Evaluation of viable cells in Pseudomonas aeruginosa biofilms by colony count and live/dead staining - Pezzoni, Magdalena (2020)
Pseudomonas aeruginosa is a human pathogen capable to form robust biofilms. P. aeruginosa biofilms represent a serious problem because of the adverse effects on human health and industry, from sanitary and economic points of view. Typical strategies to break down biofilms have been long used, such as the use of disinfectants or antibiotics, but also, according to their high resistance to standard antimicrobial approaches, alternative strategies employing photocatalysis or control of biofilm formation by modifying surfaces, have been proposed. Colony forming units (cfu) counting and live/dead staining, two classic techniques used for biofilm quantification, are detailed in this work. Both methods assess cell viability, a key factor to analyze the microbial susceptibility to given treatment, then, they represent a good approach for evaluation of an antibiofilm strategy.